Third party product reviews and consumer behaviour : A dichotomous measuring via rasch, paired comparison and graphical chain models - Ziniel, Wolfgang (Springer Fachmedien Wiesbaden, 2013)
By exploiting the potential of the Internet, independent product reviews can reach more consumers than ever before. The numerous publications of product reviews in the mass media (e.g., magazines, news services on the Internet) and on Web 2.0 are received with rising resonance that is not restricted to products of broad interest only. Apart from purely descriptive approaches, however, no systematic studies which examine the possible impacts of these tests on consumer behaviour have been presented so far. Wolfgang Ziniel combines both a theoretical and an experimental approach when investigating the relevance of product tests for product choice, product quality, value, and purchase intention from the consumers' point of view. Concerning the dichotomous measurement approach graphical chain models, Rasch- and paired comparison conjoint-models are applied.   This thesis has been granted the Stephan Koren Award for outstanding scientific achievements.     Contents ·         Perceived Quality Research ·         Customer Value ·         Rasch Modelling and Scale Development, Graphical Chain Modelling, Bradley-Terry Model ·         Third-Party Product Tests ·         Product Choice Process ·         Purchase Intentions     Target Groups ·         Academics and researchers in the fields of marketing, psychometrics, psychological consumer behaviour research ·         Practitioners in the fields of marketing, sales, product management, online marketing, Web 2.0.     Author Wolfgang Ziniel completed his doctoral thesis as a research assistant under the supervision of Prof. Reinhold Hatzinger at the Vienna University of Economics and Business. Currently he works in the field of industry and structure analyses and retail research at the Austrian Institute for SME Research in Vienna.